ANALYSIS OF BANKS ACTIVITIES THAT HAVE SUCCESSFULLY IMPLEMENTED DIGITAL INNOVATIONS IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
The article focuses on analysis of banks activities that have successfully implemented digital innovations in Uzbekistan. The main tendencies and measures, concerned to digitalization of banking and financial operations were researched.